A novel method for estimating carbon emission based on industrial metabolism: Blast furnace iron-making with micro mechanism model. (November 2022) - Chen, Junwen; Zhang, Hua; Zhao, Gang; Qureshi, Abdul Samad
Abstract: The carbon emission accounting method provided by IPCC depends heavily on the emission coefficients of various types of fossil fuels. Literature reviews present the emission coefficients are usually assigned widely in various industrial systems, due to the absence of considerations on the mechanism and process of carbon emissions. It seems more suitable for estimating the massive carbon emissions at a macro level of a region or country, with tolerable estimating errors. For more accurate carbon accounting and prediction, it is crucial to develop a novel methodology on a micro mechanism model that is independent of the historical data and emission coefficients for a given industrial system at a micro level. Via analysing the mass energy balances and simulating the industrial metabolic pathways, instead of using the emission coefficients, a micro mechanism model of blast-furnace iron-making system is established based on the network of industrial metabolism, for offering an alternative carbon accounting methodology. In the case study, a network of industrial metabolism is established on the fundamental chemical reactions that is conducted in the blast-furnaces and the iron-making system. The metabolic simulation shows the dynamic change curves of metabolic variables at each moment. As a result, the carbon emission intensities estimated by IPCC, WSA, JM, WRI, EC, and IM methods are respectively 831.61 kg, 1500.00 kg, 1171.6 kg, 1381.64 kg, 792.45 kg, and 647.82 kg per ton of molten iron. The bias in the carbon accounting primarily results from the differences of boundary conditions. Generally, the novel carbon accounting methodology based on the industrial metabolism better indicates the carbon emissions at a micro level for the iron-making systems under China's industrial conditions.